2021
DOI: 10.3389/fcell.2020.609683
|View full text |Cite
|
Sign up to set email alerts
|

MiT/TFE Family of Transcription Factors: An Evolutionary Perspective

Abstract: Graphical AbstractMiT/TFE transcription factors are master regulators of cellular adaptation to a wide variety of stressful conditions. They control the expression of a plethora of genes involved in response to nutrient deprivation, oxidative and ER stress, and DNA and mitochondrial damage. MiT/TFE proteins play a critical role in organelle biogenesis, control of energy homeostasis, adaptation to pathogen infection, control of growth and development, aging, and death. MiT/TFE proteins are also modulators of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 160 publications
0
39
0
Order By: Relevance
“…The TFEB belongs to the microphthalmia/transcription factor E (MiT/TFE) family of helix–loop–helix-leucine-zipper (bHLH- Zip) proteins. TFEB regulates the expression of genes involved in the autophagy–lysosomal pathway ( Puertollano et al, 2018 ; La Spina et al, 2021 ). It also regulates autophagic flux by promoting and regulating lysosomal and autophagosome biogenesis and regulating autophagosome-lysosome fusion, thereby; facilitating cellular clearance ( Settembre et al, 2011 ).…”
Section: Vital Transcription Factors In Alzheimer’s Diseasementioning
confidence: 99%
“…The TFEB belongs to the microphthalmia/transcription factor E (MiT/TFE) family of helix–loop–helix-leucine-zipper (bHLH- Zip) proteins. TFEB regulates the expression of genes involved in the autophagy–lysosomal pathway ( Puertollano et al, 2018 ; La Spina et al, 2021 ). It also regulates autophagic flux by promoting and regulating lysosomal and autophagosome biogenesis and regulating autophagosome-lysosome fusion, thereby; facilitating cellular clearance ( Settembre et al, 2011 ).…”
Section: Vital Transcription Factors In Alzheimer’s Diseasementioning
confidence: 99%
“…2 ). TFEB is a member of the microphthalmia‐associated family of the basic helix‐loop‐helix (b‐HLH) leucine zipper transcription factor (MiT/TFE) family of transcription factors, including MiTF, TFE3, TFEB, and TFEC [ 33 ]. Upon activation, TFEB translocates to the nucleus and binds to the coordinated lysosomal expression and regulation (CLEAR, also known as E‐boxes) elements (GTCACGTAC) enriched in the promoter region of numerous lysosomal and autophagic genes, activating the coordinated transcription of these two sets of genes [ 31 , 32 , 34 ].…”
Section: Coordinated Regulation Of Lysosomal Biogenesis and Autophagy...mentioning
confidence: 99%
“…The authors also showed that nuclear TFEB favored lysosomal-exocytosis-mediated IL-β secretion, a pro-inflammatory cytokine that has been related to impair insulin secretion and shown to contribute to chronic inflammation reported in type 2 diabetes mellitus patients [ 78 , 79 ], strengthening the idea that although there is evidence that TFEB activation can promote a response that helps the cell to deal with stress, under specific circumstances it could trigger detrimental effects. The C. elegans TFEB ortholog is HLH-30 [ 80 , 81 ]. HLH-30/TFEB is predominantly localized in the cytoplasm under basal conditions and translocates into the nucleus upon several cellular stresses, such as lysosomal impairment, bacterial infection, prolonged endoplasmic reticulum (ER) stress, reactive oxygen species (ROS), and nutrient scarcity [ 82 , 83 , 84 , 85 ].…”
Section: Impacts Of Carbohydrate Metabolism On Lifespanmentioning
confidence: 99%